2021
DOI: 10.1039/d1ra00944c
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired modified graphene oxide/polyurethane composites with rapid self-healing performance and excellent mechanical properties

Abstract: We successfully modified graphene oxide with amino-terminated hyperbranched polyamide(MGO), and obtained novel mussel-inspired MGO/polyurethane composites with outstanding self-healing and mechanical performances via rational molecular design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…The highest tensile strength of 6.97 MPa is achieved, when the BDB content is 20%, due to the highest cross-link density (16.4 × 10 −4 mol/cm 3 ). In comparison with recent reported HTPB-based PU vitrimer [35][36][57][58] as Figure 10 shown, it is found high mechanical properties in this work. It results from a incorporation of soft HTPB and rigid HPS, MDI, BDB with benzene ring, and physical cross-links formed by hydrogen bonds.…”
Section: Mechanical Properties Thermal Performance and Dynamic Proper...supporting
confidence: 53%
See 1 more Smart Citation
“…The highest tensile strength of 6.97 MPa is achieved, when the BDB content is 20%, due to the highest cross-link density (16.4 × 10 −4 mol/cm 3 ). In comparison with recent reported HTPB-based PU vitrimer [35][36][57][58] as Figure 10 shown, it is found high mechanical properties in this work. It results from a incorporation of soft HTPB and rigid HPS, MDI, BDB with benzene ring, and physical cross-links formed by hydrogen bonds.…”
Section: Mechanical Properties Thermal Performance and Dynamic Proper...supporting
confidence: 53%
“…As shown in Figure 10, ref. [35,38,58,72,73] reported that HTPB-based PU vitrimers show remarked self-healing properties at low temperature, while tensile strength is low. Meanwhile, the HTPB-based PU vitrimers in ref.…”
Section: Self-healing and Welding Propertiesmentioning
confidence: 99%
“…As shown in Figure 3 b, a new signal, N1s at 400.1 eV, appears in the spectra of PDA@CNFs, and N1s accounts for 3.61% of PDA@CNFs. Figure 3 c shows the UV-VIS spectra chemical polymerization of DA after 24 h at 25 °C, and PDA@CNFs shows two broad peaks at around 280 nm and 405 nm in the aqueous solution, which are suggested as evidence for the oxidation self-polymerization of DA [ 41 , 42 ]. For CNFs, the XPS C1s spectrum can be curve-fitted with four peak components at the binding energy of 284.8 eV, 286.6 eV, 289.0 eV and 291.1 eV, attributable to the C-C, C-O, O=C-O and π-π species, respectively, as shown in Figure 3 d. However, for PDA@CNFs, the XPS C1s spectra shows a new peak at 285.5 eV, which represents C-N (see Figure 3 e).…”
Section: Resultsmentioning
confidence: 99%
“…4h). 25,[45][46][47][48][49][50][51][52][53][54] The poly(TA)/Al composite elastomers can rapidly repair damage and self-heal and is thus a promising candidate for operation in harsh environments.…”
Section: Self-healing and Reprocessing Properties Of Poly(ta)/al Comp...mentioning
confidence: 99%